Combined effect of silicon dioxide nanoparticles and plant-derived smoke solution on physiological and biochemical parameters of pea plant (Pisum sativum L.) - Momin, Abdul; Naheed, Rafia; Jamil, Muhammad; Rehman, Shafiq ur; Khatoon, Amana; Rha, Eui Shik (International Journal of Applied and Experimental Biology, 2024)
Nanomaterials exhibit distinctive advantages due to their characteristic size range falling within 1-100 nanometers, which can easily penetrate through plant cell membranes. The application of plant-derived smoke (PDS) solutions is also recognized for its beneficial impact on seed germination and growth of diverse plant species. In this context, in the present study, we investigated the effects of silicon dioxide nanoparticles (SiO2 NPs), PDS, and their combined application on pea seeds, and thereafter evaluated a spectrum of morphological and biochemical growth parameters. The results demonstrated that SiO2 NPs significantly enhanced pea seed germination, seedling length/weight, secondary root formation, as well as key biochemical indicators including photosynthetic pigments, total soluble sugars, and protein content. Notably, the PDS solution also exerted a significant positive influence on all growth parameters in comparison to that of SiO2 NPs. However, the combined application of SiO2 NPs and PDS exhibited superior effects on the morphological and biochemical growth characteristics as compared to their individual applications. From these findings, it can be concluded that both SiO2 NPs and PDS solutions, whether used independently or in combination, impart beneficial effects on the morphological and biochemical growth parameters of pea plants. This research highlights the potential of SiO2 NPs and PDS solutions as promising tools for enhancing plant growth and seedling development. Future studies could further explore the underlying mechanisms and optimize application methods for maximizing the beneficial effects of these materials, thus contributing to sustainable agricultural practices and improved crop yields.